2020
DOI: 10.3390/agronomy10020247
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Traits of Fermented Alfalfa Brown Juice: Its Implications on Physiological, Biochemical, Anatomical, and Growth Parameters of Celosia

Abstract: Brown juice is a byproduct of fractionated green biomass during leaf protein isolation. It represents approximately 45%–50% of the total pressed fresh biomass. Disposal of brown juice is a serious issue in leaf protein production due to its high biological oxygen demand and carbohydrates content. The current study aimed to find a possible potential use of brown juice. Therefore, chemical and biochemical properties of brown juice—derived from alfalfa green biomass—were determined before and after fermentation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…Depending on the specific processing techniques, the color of brown juice may vary from yellowish-brown to dark brown or green. This brown juice can be applied as a bio-organic fertilizer to promote crop growth and as a medium for microbial growth (Shende & Gogle, 2016;Bákonyi et al, 2020). The biorefining process of alfalfa has positive impacts not only on the environment but also on human health, which could be expected using novel protein sources (De Corato et al, 2018;Kaszás et al, 2020).…”
Section: The Bio-organic Fertilizers Derived From Alfalfamentioning
confidence: 99%
“…Depending on the specific processing techniques, the color of brown juice may vary from yellowish-brown to dark brown or green. This brown juice can be applied as a bio-organic fertilizer to promote crop growth and as a medium for microbial growth (Shende & Gogle, 2016;Bákonyi et al, 2020). The biorefining process of alfalfa has positive impacts not only on the environment but also on human health, which could be expected using novel protein sources (De Corato et al, 2018;Kaszás et al, 2020).…”
Section: The Bio-organic Fertilizers Derived From Alfalfamentioning
confidence: 99%
“…Bákonyi et al [31] and Kisvarga et al [32] reported that alfalfa brown juice could be considered a potential growth stimulator. In their studies, Celosia seedlings where sprayed at five increasing rates of fermented brown juice (0.5%, 1.0%, 1.5%, 2.0% or 2.5%), while basil was sprayed at three different increasing doses (0.5%, 1.0% or 2.5%).…”
Section: The Role Of Non-microbial and Microbial Biostimulants In Mormentioning
confidence: 99%
“…A recently-developed and novel technology enables the production of large amounts of an environmentally-friendly alfalfa-based organic biostimulant called brown juice (BJ), which is a by-product of leaf protein concentrate (LPC) [2]. The pH of fresh BJ varies between 5 and6, and it contains several biologically-active components, including phenols, amino acids, macro-and microelements, carbohydrates (40%), and nitrogen (3%) on a dry mass basis [3][4][5]. Due to its high sugar content, fresh BJ spoils within a week of storage at room temperature.…”
Section: Introductionmentioning
confidence: 99%